Management News and Notes: Academy of Management News (Academy of Management Journal, 1965)
The article presents news and notes from the Academy of Management. Fellows newly elected include Paul J. Gordon (Indiana University), Burnard H. Sord (University of Texas), and R. Stansbury Stockton (Indiana University). News and meeting notices for the Eastern, Midwest, Southern, Southwest, and Southern Divisions of the Academy are noted.